2012
DOI: 10.1093/jpids/pis052
|View full text |Cite
|
Sign up to set email alerts
|

Use of Administrative Data for the Identificationof Laboratory-Confirmed Influenza Infection: The Validity ofInfluenza-Specific ICD-9 Codes

Abstract: We used Pediatric Health Information System data and laboratory records from 3 children's hospitals to determine whether administrative data accurately identify children with laboratory-confirmed influenza. Among 23 282 inpatients, diagnosis codes for influenza detected 73% of laboratory-confirmed influenza cases, whereas <1% of patients without a diagnosis code had laboratory-confirmed influenza.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 7 publications
2
46
0
Order By: Relevance
“…However, in hospitalized patients, guidelines for most of the ICD‐10 codes require identification of influenza virus and tests for influenza are easily available with no restrictions on use. Studies indicate that the ICD‐codes tend to underestimate the number of influenza cases, however, the specificity of the ICD‐codes is shown to be high, indicating that the ICD‐codes of influenza are likely to reflect true influenza infection. In addition, many patients with influenza might not be tested for influenza or tested too late to confirm the diagnosis and may therefore be registered with other diagnoses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in hospitalized patients, guidelines for most of the ICD‐10 codes require identification of influenza virus and tests for influenza are easily available with no restrictions on use. Studies indicate that the ICD‐codes tend to underestimate the number of influenza cases, however, the specificity of the ICD‐codes is shown to be high, indicating that the ICD‐codes of influenza are likely to reflect true influenza infection. In addition, many patients with influenza might not be tested for influenza or tested too late to confirm the diagnosis and may therefore be registered with other diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…However, in hospitalized patients, guidelines for most of the ICD-10 codes require identification of influenza virus and tests for influenza are easily available with no restrictions on use. Studies indicate that the ICD-codes tend to underestimate the number of influenza cases,[42][43][44] however, the specificity of the ICD-codes is shown to be high, indicating that the ICD-codes of in-…”
mentioning
confidence: 99%
“…15 Studies estimating validity of ICD diagnosis codes for the identification of laboratory-confirmed influenza have shown mixed results. 14,[16][17][18] So far, few studies have looked at accuracy of RSVspecific ICD-10 diagnosis codes for the identification of true RSV infections. To our knowledge, only Pisesky et al 19 reported high sensitivity (97.9%, 95%-CI: 95.5%-99.2%) and specificity (99.6%, 95%-CI: 98.2%-99.8%) of RSV-specific ICD-10 codes for the identification of hospitalized RSV among children.…”
Section: Seed Arementioning
confidence: 99%
“…However, in previous studies, ICD-9-CM codes have been shown to have high specificity and positive predictive value for identifying children hospitalized with laboratory-confirmed influenza. 26,27 Third, although we attempted to adjust for confounding by indication by using propensity score matching, additional important patient and hospital characteristics, such as influenza vaccination status and duration of illness before admission, are not available from the database. These patient-level and hospital-level factors could not be included in our propensity score but may have influenced anti-influenza medication prescribing patterns and study outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…These ICD-9-CM codes have been previously used to identify hospitalized pediatric patients with the presence of tracheostomy 19,21,25 and laboratoryconfirmed influenza with high specificity and positive predictive value. [26][27][28][29] We excluded patients with any of the following characteristics: (1) age 20 years or older to exclude adult patients; (2) transfer from an outside hospital with inpatient status, given interest in initial treatment of influenza and length of stay (LOS); (3) extreme outliers in LOS defined as median plus 3 times the interquartile range (IQR); (4) death during the index hospitalization because the patients could not have a revisit; (5) presence of surgical procedures unrelated to influenza within first 2 days of hospitalization to minimize the possibility of including patients who acquired or manifested with influenza infection during hospitalizations for other reasons; or (6) missing variables in the database. To prevent overrepresentation by patients with multiple eligible encounters, we first assigned a computer-generated random whole number to each admission episode and subsequently selected 1 admission episode for each patient for analysis.…”
Section: Patient Selectionmentioning
confidence: 99%